Atmospheric deposition of Pb and Cd in the Cedrus atlantica for environmental biomonitoring - Isinkaralar, Kaan (Landscape and ecological engineering, 2022)
Atmospheric heavy metal deposition is widely occurring due to anthropogenic effects such as industrial activities and motor vehicles. As a result, it has increased significantly and reached a level that threatens human health and the environment. Among these deposition factors, it is of great importance to monitor the atmospheric concentrations of heavy metals that do not easily degrade in nature, tend to bioaccumulate, and can be toxic even at low concentration levels. Biomonitoring is one of the most impressive passive methods in determining the change of heavy metal concentrations in the atmosphere. This study investigates the effect of anthropogenic emission sources in urban areas using tree rings as a biomonitor. Cedrus atlantica was selected, because it is generally preferred in parks, roadside and landscape design. Samples were collected from parks near the road, densely populated, and close to the small-scale industry in Kastamonu, Türkiye. Atmospheric deposition of Lead (Pb) and Cadmium (Cd) in organs were analyzed based on years and directions. Their accumulation in the outer bark was determined to be quite high (Cd value is 2226.2 ppb and Pb value is 38201.1 ppb) compared to other organs. As a result, the traffic density and industrial emissions affect the Pb and Cd concentrations. This study will provide beneficial information for atmospheric heavy metal deposition in landscape plants.